2021
DOI: 10.1186/s12913-021-06524-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient volume and quality of primary care in Ethiopia: findings from the routine health information system and the 2014 Service Provision Assessment survey

Abstract: Background Several studies have reported inadequate levels of quality of care in the Ethiopian health system. Facility characteristics associated with better quality remain unclear. Understanding associations between patient volumes and quality of care could help organize service delivery and potentially improve patient outcomes. Methods Using data from the routine health management information system (HMIS) and the 2014 Ethiopian Service Provision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
6
10
0
Order By: Relevance
“…Quality decreased with increasing patient volume in health facilities that treated 90.6 or more patients per day, while quality increased with increasing patient volume in health facilities that treated fewer than 90.6 patients per day in the outpatient departments. 51 Our finding is consistent with a study at public hospitals in China where overcrowding was negatively associated with clients’ perception of quality of care. 31 The apparent correlation between patient volume and PQoC could be explained by factors such as increased demand for healthcare providers and longer wait times.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Quality decreased with increasing patient volume in health facilities that treated 90.6 or more patients per day, while quality increased with increasing patient volume in health facilities that treated fewer than 90.6 patients per day in the outpatient departments. 51 Our finding is consistent with a study at public hospitals in China where overcrowding was negatively associated with clients’ perception of quality of care. 31 The apparent correlation between patient volume and PQoC could be explained by factors such as increased demand for healthcare providers and longer wait times.…”
Section: Discussionsupporting
confidence: 91%
“…A study in Ethiopia identified a non-linear significant association (an inverted U-shape) between patient volume and quality. Quality decreased with increasing patient volume in health facilities that treated 90.6 or more patients per day, while quality increased with increasing patient volume in health facilities that treated fewer than 90.6 patients per day in the outpatient departments 51. Our finding is consistent with a study at public hospitals in China where overcrowding was negatively associated with clients’ perception of quality of care 31.…”
Section: Discussionsupporting
confidence: 87%
“…Quality decreased with increasing patient volume in health facilities that treated 90.6 or more patients per day, while quality increased with increasing patient volume in health facilities that treated less than 90.6 patients per day in the outpatient departments. 50 Our finding is consistent with a study at public hospitals in China, 30 where overcrowding was negatively associated with clients’ perception of quality of care. There are two possible explanations for the observed relationship between patient volume and PQoC.…”
Section: Discussionsupporting
confidence: 91%
“…This finding assured that the provision of quality service by the public health facilities was poor. The main reason could be the lack of skilled professionals and shortage of equipment due to poverty, although this result is in line with a study conducted in Ethiopia [27].…”
Section: Discussionsupporting
confidence: 86%